Analisis Miskonsepsi Siswa Pada Materi Hukum Dasar Kimia Menggunakan Two-Tier Diagnostic Test Di SMA Negeri 1 Tatapaan - Claudya Gabby Lahinda; Jeanne M Tuerah (Oxygenius Journal Of Chemistry Education, 2022)
Misconception is a concept that is not in accordance with the scientific understanding or concepts recognized by experts. Student misconceptions are found while at school when learning in class, from experience, and their observations in society or in everyday life. Students' misconceptions are also obtained through their knowledge at the previous school level. This research aims to analyzing students' misconceptions on basic chemical law material at SMA Negeri 1 Tatapaan. Data collection was in the form of two-tier diagnostic test questions, which were tested on 13 students. The data analysis used in this study is the Rasch model. From the results of the study it was concluded that 62% of students who understood the concept, and 23% of students who experienced misconceptions, while 15% of students who did not understand the concept of basic chemistry law material.